Synthesis of Copolymer from Industrial Waste as Modifier for Iraqi Lubricants - Zainab Kadhim Al-Khazragie; Haneen H. Talib; Zuhoor Jawad Younis; Sabah Abbas Malık; Ali Faisal Hussein (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The increasing global demand for sustainable practices in the lubricants industry has highlighted the potential for utilizing industrial waste to enhance lubrication formulations. Specifically, the use of polyethylene wax derived from industrial waste offers a promising avenue for improving polymer performance. Specific Background: In Iraq, the development of lubricating oil formulations utilizing locally sourced industrial waste remains underexplored. The synthesis of copolymers from polyethylene wax and alkyl acrylates presents a novel approach to improving the efficiency of lubricants. Knowledge Gap: While numerous studies have focused on the role of polymer additives in lubrication, there is a lack of research on the application of waste-derived copolymers, particularly in the context of the Iraqi oil industry. Aim: This study investigates the synthesis and characterization of poly(2-ethylhexyl acrylate-co-polyethylene wax) (TND-W) copolymer derived from industrial waste, and evaluates its efficacy as a viscosity modifier (VM) and pour point depressant (PPD) in lubricating oils. Results: The synthesized copolymer demonstrated significant improvements in the viscosity and pour point properties of base oils. The copolymer's performance was shown to be concentration-dependent, with the optimal performance observed at 4000 ppm. However, increasing the concentration beyond this level resulted in reduced effectiveness due to solubility limitations in the base oils, especially at lower temperatures. Novelty: This research introduces a sustainable approach to enhancing lubricating formulations by utilizing industrial waste materials, a method not commonly explored in previous studies within the context of the Iraqi oil industry. Implications: The findings provide valuable insights for the oil industry, particularly in the development of eco-friendly lubricants. The study's implications extend to environmental sustainability, suggesting a practical solution for incorporating waste-derived materials into industrial applications. Highlights: Synthesis of a copolymer from industrial waste for use in lubricating oils. Demonstrated the copolymer's dual functionality as a viscosity modifier and pour point depressant. Highlighted the concentration-dependent effectiveness of the copolymer, with optimal performance at 4000 ppm. Offered a sustainable approach to improving oil formulations, contributing to both environmental and performance enhancement. Keywords: Copolymer, Lubricating Oil, Polyethylene Wax, Pour Point Depressant, Viscosity Modifier (VM)